From Two Worlds. - Jantjes, Gavin; Serota, Nicholas; Solanke, Adeola (London : Whitechapel Art Gallery, 1986)
Araeen, Rasheed ; Arif, Saleem ; Beckford, Franklyn ; Ben-David, Zadok ; Bhimji, Zarina ; The Black Audio Film Collective ; Boyce, Sonia ; Camp, Sokari Douglas ; Forrester, Denzil ; Himid, Lubaina ; Jantjes, Gavin ; Joseph, Tam ; Niati, Houria ; Piper, Keit ; Ryan, Veronica ; Uddin, Shafique
From Two Worlds, Whitechapel Art Gallery, London, 30 July - 7 September 1986
boek